Big Business and the Crisis of German Democracy - Bisno, Adam (Cambridge University Press, 2024)
Explains why the liberalism of a group of elites, the owners of Berlin's grand hotels, gave way to a more aggressive nationalism and conservatism after World War I – a shift which contributed directly to Hitler's rise to power. This title is also available as open access on Cambridge Core.